2012
DOI: 10.1590/s1020-49892012000100004
|View full text |Cite
|
Sign up to set email alerts
|

Religião e fecundidade entre adolescentes no Brasil

Abstract: The results presented in this study are encouraging insofar as they show that Protestant adolescents, particularly Pentecostals, have a reduced risk of adolescent premarital motherhood. This result was not expected, given that Pentecostalism predominates in the less advantaged population groups, with lower incomes and levels of education and residence in urban areas, where adolescent fertility is also concentrated in Brazil. Future studies must be undertaken with the purpose of understanding how the various me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0
8

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 10 publications
2
6
0
8
Order By: Relevance
“…Our findings corroborate those of McKinnon, Potter, and Garrard-Burnett (2008) and Verona and Dias Junior (2012), and reveal that young women who belonged to Pentecostal churches at the time of the interview were at a lower risk of engaging in adolescent premarital first sexual intercourse than those who belonged to the Catholic Church. In addition, the risk of premarital sexual initiation during adolescence was also lower among girls who currently attended religious services regularly as compared to those who never participated, even after demographic and socioeconomic variables, also measured at the time of the interview, were controlled.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our findings corroborate those of McKinnon, Potter, and Garrard-Burnett (2008) and Verona and Dias Junior (2012), and reveal that young women who belonged to Pentecostal churches at the time of the interview were at a lower risk of engaging in adolescent premarital first sexual intercourse than those who belonged to the Catholic Church. In addition, the risk of premarital sexual initiation during adolescence was also lower among girls who currently attended religious services regularly as compared to those who never participated, even after demographic and socioeconomic variables, also measured at the time of the interview, were controlled.…”
Section: Discussionsupporting
confidence: 89%
“…It also notes that adolescents who belong to the Assembly of God, other Pentecostal Protestant, or other mainline Protestant churches are much more likely to be married than Catholics. More recently, Verona and Dias Junior (2012) found that adolescent females who showed higher attendance at religious services and belonged to Pentecostal churches at the time of the interview have lower risk of showing adolescent premarital fertility in 1996 and 2006, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…(1) International studies report that one third of all American girls will become pregnant by the time they are 20 years old. (2) Data indicate that besides the relative increase in pregnancy among adolescent women, the same increase occurs among women older than 30 years.…”
Section: Introductionmentioning
confidence: 99%
“…15 been also pointing to the association among religion, fertility, abortion, and sexual behavior in Brazil. [16][17][18][19][20][21] Protestant women tend to have lower fertility levels in comparison to catholic women. 21 Women who self-declared being traditional protestants presented the lowest levels of fertility.…”
Section: Background 21 Fertility Declinementioning
confidence: 99%